Theoretical study of the Alfven eigenmode stability in CFETR steady state discharges. (20th January 2022) - Varela, J.; Huang, J.; Spong, D.A.; Chen, J.; Chan, V.; Garcia, L.; Wingen, A.; Ghai, Y.; Zou, Y.
Abstract: The aim of this study is to analyze the stability of Alfven eigenmodes (AE) in the China Fusion Engineering Test Reactor (CFETR) plasma for steady state operations. The analysis is done using the gyro-fluid code FAR3d including the effect of the acoustic modes, EP finite Larmor radius damping effects and multiple energetic particle populations. Two high poloidal β scenarios are studied with respect to the location of the internal transport barrier (ITB) at r / a ≈ 0.45 (case A) and r / a ≈ 0.6 (case B). Both operation scenarios show a narrow TAE gap between the inner-middle plasma region and a wide EAE gap all along the plasma radius. The AE stability of CFETR plasmas improves if the ITB is located inwards, case A, showing AEs with lower growth rates with respect to the case B. The AEs growth rate is smaller in the case A because the modes are located in the inner-middle plasma region where the stabilizing effect of the magnetic shear is stronger with respect to the case B. Multiple EP populations effects (NBI driven EP + alpha articles) are negligible for the case A, although the simulations for the case B show a stabilizing effect of the NBI EP on the n = 1 BAE caused by α particles during the thermalization process. If the FLR damping effects are included in the simulations, the growth rate of the EAE/NAE decreases up to 70%, particularly for n > 3 toroidal families. Low n AEs ( n < 6) show the largest growth rates. On the other hand, high n modes ( n = 6 to 15) are triggered in the frequency range of the NAE, strongly damped by the FLR effects.